(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Hypertrophic gingivitis is a chronic inflammatory disease of the periodontal tissues characterized by an increase in the volume of the gingival margin and interdental papillae. This condition not only compromises oral aesthetics but also creates niches for pathogenic microflora, potentially leading to periodontitis. This article explores the multifactorial etiology of the disease—ranging from local dental factors to systemic hormonal shifts—classifies its clinical forms, and evaluates modern therapeutic approaches including pharmacological and surgical interventions.